Climate Change Impact on Agriculture in India - Reddy, D. Raji; Sreenivas, G. (International Journal of Economic Plants, 2016)
Human influence on the climate system is clear, and recent anthropogenic emissions of greenhouse gases are the highest in history. Recent climate changes have had widespread impacts on human and natural systems. Climate change or global warming is caused by the release of ‘greenhouse’ gases into the atmosphere. These gases accumulate in the atmosphere and increase the effect of radiative forcing on the climate, resulting in a warming of the atmosphere. The changes in greenhouse gas concentrations are projected to lead to regional and global changes in climate and weather parameters such as temperature, precipitation, soil moisture, and sea level. Agriculture is one sector that is important to consider in terms of climate change. The agriculture sector both contributes to climate change, as well as will be affected by the changing climate. Climate change will have an economic impact on agriculture, including changes in farm profitability, prices, supply, demand and trade. Recent climate changes have had widespread impacts on human and natural systems. Warming of the climate system is unequivocal, and since the 1950s, many of the observed changes are unprecedented over decades to millennia.Specific measures can only provide a successful adaptive response if they are adopted in appropriate situations. A variety of issues need to be considered, including land-use planning, watershed management, disaster vulnerability assessment, consideration of port and rail adequacy, trade policy, and the various programmes countries use to encourage or control production, limit food prices, and manage resource inputs to agriculture.